Application of Restorative Justice in Health Crime - Retnaningrum, Dwi Hapsari; Wahyudi, Setya; Budiyono, Budiyono; Nugroho, Norcha Satria Adi (Jurnal Dinamika Hukum, 2023)
Health sectors covers wide range of criminal acts, including medical malpractice, circulation of illegal drug, pharmacy and prescription drug fraud, and hospital unprofessionalism. The Number of victims due to crimes in health sector is far more than what it appears to be. An example of crimes within the health sectors is medical malpractice. Malpractice is a bad practice. Restorative justice as new approach offers a solution to criminal cases that focus more on the recovery rather than vengeance. Therefore, the issue that need to be discuss is whether health crimes equate to medical malpractice and how should the application of restorative justice be applied to criminal acts in health sectors. One of the main reasons to implement restorative justice is because the victim as the party who is most harmed and suffers, is in fact generally being abandoned in criminal justice system. The care and protection given to the victim felt not yet adequate especially if the aim is to restore the victim’s suffering. This study shows that health crimes does not equate to medical malpractice because as the name suggested medical malpractice entail a profession. However, criminal acts can be committed by anyone. The application of restorative justice should be applied to cases in health sectors that involve negligence and not cases based on intent. The application of restorative justice can be beneficial to perpetrators, victims, and society. Keywords: restorative justice, malpractice, health crime